2018
DOI: 10.1126/science.aat6752
|View full text |Cite
|
Sign up to set email alerts
|

High-affinity adsorption leads to molecularly ordered interfaces on TiO 2 in air and solution

Abstract: Researchers around the world have observed the formation of molecularly ordered structures of unknown origin on the surface of titanium dioxide (TiO) photocatalysts exposed to air and solution. Using a combination of atomic-scale microscopy and spectroscopy, we show that TiO selectively adsorbs atmospheric carboxylic acids that are typically present in parts-per-billion concentrations while effectively repelling other adsorbates, such as alcohols, that are present in much higher concentrations. The high affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
198
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(216 citation statements)
references
References 27 publications
15
198
3
Order By: Relevance
“…The interaction of H 2 O with R‐TiO 2 (110) in UHV has been largely investigated using a series of experimental techniques, such as TPD, STM, two‐photon photoemission (2PPE), and infrared reflection absorption spectroscopy (IRAS) . It is well‐established that H 2 O molecules dissociatively adsorb at the O v sites (H 2 O v ) and the 〈111〉‐oriented steps, forming OH groups on the O b rows (OH b s) .…”
Section: Reaction Mechanisms In Tio2 Photocatalysismentioning
confidence: 99%
“…The interaction of H 2 O with R‐TiO 2 (110) in UHV has been largely investigated using a series of experimental techniques, such as TPD, STM, two‐photon photoemission (2PPE), and infrared reflection absorption spectroscopy (IRAS) . It is well‐established that H 2 O molecules dissociatively adsorb at the O v sites (H 2 O v ) and the 〈111〉‐oriented steps, forming OH groups on the O b rows (OH b s) .…”
Section: Reaction Mechanisms In Tio2 Photocatalysismentioning
confidence: 99%
“…Refs. [20,[34][35][36][37]. Water dissociation is often affected by specific atomic defects such as oxygen vacancies as mentioned above, impeding conclusive answers for the intrinsic property of the stoichiometric TiO 2 [38][39][40][41][42][43].…”
mentioning
confidence: 99%
“…Normally the monolayer of carboxylic acid formed on the surface of the TiO 2 makes the TiO 2 film hydrophobic but when we expose the UV light, it decomposes the organic molecules and makes the substrate hydrophilic. Recently, Balajka et al has reported this by utilizing the atomic‐scale microscopy tool to investigate the origin of hydrophilicity of the TiO 2 thin films.…”
Section: Resultsmentioning
confidence: 99%